Highly Dispersed Ni Nanoclusters Spontaneously Formed on Hydrogen Boride Sheets - Natsumi Noguchi; Shin-ichi Ito; Miwa Hikichi; Yohei Cho; Kazuho Goto; Atsushi Kubo; Iwao Matsuda; Takeshi Fujita; Masahiro Miyauchi; Takahiro Kondo (Molecules, 2022)
Hydrogen boride (HB) sheets are two-dimensional materials comprising a negatively charged hexagonal boron network and positively charged hydrogen atoms with a stoichiometric ratio of 1:1. Herein, we report the spontaneous formation of highly dispersed Ni nanoclusters on HB sheets. The spontaneous reduction reaction of Ni ions by the HB sheets was monitored by in-situ measurements with an ultraviolet-visible spectrometer. Acetonitrile solutions of Ni complexes and acetonitrile dispersions of the HB sheets were mixed in several molar ratios (the HB:Ni molar ratio was varied from 100:0.5 to 100:20), and the changes in the absorbance were measured over time. In all cases, the results suggest that Ni metal clusters grow on the HB sheets, considering the increase in absorbance with time. The absorbance peak position shifts to the higher wavelength as the Ni ion concentration increases. Transmission electron microscopy images of the post-reaction products indicate the formation of Ni nanoclusters, with sizes of a few nanometers, on the HB sheets, regardless of the preparation conditions. These highly dispersed Ni nanoclusters supported on HB sheets will be used for catalytic and plasmonic applications and as hydrogen storage materials.